Nanomechanically visualizing drug-cell interaction at the early stage of chemotherapy - Wu, Yun-Long (2020)
A detailed understanding of chemotherapy is determined by the response of cell to the formation of the drug-target complex and its corresponding sudden or eventual cell death. However, visualization of this early but important process, encompassing the fast dynamics as well as complex network of molecular pathways, remains challenging. Herein, we report that the nanomechanical traction force is sensitive enough to reflect the early cellular response upon the addition of chemotherapeutical molecules in a real-time and noninvasive manner, due to interactions between chemotherapeutic drug and its cytoskeleton targets. This strategy has outperformed the traditional cell viability, cell cycle, cell impendence as well as intracellular protein analyses, in terms of fast response. Furthermore, by using the nanomechanical traction force as a nanoscale biophysical marker, we discover a cellular nanomechanical change upon drug treatment in a fast and sensitive manner. Overall, this approach could help to reveal the hidden mechanistic steps in chemotherapy and provide useful insights in drug screening.